Relationship between Plumage Colour and Egg Production Traits in Native Chicken (Indian Journal of Animal Production and Management, 2024)
Present study was conducted in Bidar district of Karnataka, where 150 eggs were collected from  surrounding five different villages. The eggs were hatched with 67% hatchability. Chicks were reared  with all standard managemental practices. Twenty healthy female birds of different plumage colour  namely brown, black and black with yellow tinge were selected and separated into three different  pens before the laying stage (at 16th week). The first lay was observed in the brown plumage colour  birds at 20th week of age followed by black and black with yellow tinge-coloured birds. Total number  of egg produced, external qualities like egg weight, egg length, egg width and shape index were  studied. The total number of eggs produced in brown, black & black with yellow tinge were 468, 411  and 392 eggs, respectively. The study showed that brown coloured birds laid more eggs with  significantly higher egg weight than other two coloured birds. Differences in egg length and egg width  were statistically significant (P
Keywords: Plumage colour; Shape index; Native chicken